Znaczenie Giełdy Transportowej dla współczesnych przedsiębiorstw produkcyjnych, transportowych i spedycyjnych na przykładzie giełdy Trans.eu - Palczewska, Anna; Barwiński, Szymon; Borowiecki, Łukasz (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
Article points out the essential elements of the freight exchanges and their usefulness to the business: manufacturing, shipping, and transportation. They addressed the issues are the four most popular freight exchange operating in Poland. Authors summarized their features and costs, presented in numbers allowing to compare them. Is discussed in detail one of the stock exchanges Trans.eu transport because of the authors' most experience in working particular with this program.